The use of Twitter to facilitate sharing of clinical expertise in urology. (7th June 2017) - Sternberg, Kevan M; Loeb, Stacy L; Canes, David; Donnelly, Laura; Tsai, Mitchell H
Abstract: The use of social media in the urologic community is common and increasing. Although the potential benefits of platforms like Twitter have been described in the literature, the use of social media in the clinical context of Urology has not been explored. In this case report, we describe how we used Twitter to share ideas about the clinical management of a complex urologic patient. By posting a clinical scenario, a timely discussion was generated with global participation and expert suggestions. This knowledge was applied to the surgical management of a patient with positive clinical outcomes. The ability of Twitter to facilitate rapid communication with a wide network of contributors makes it a potentially useful tool for clinical decision making. Care must be taken to ensure patient confidentiality and caution used appropriately when evaluating the sources and content of the clinical information shared.